2013
DOI: 10.1001/jamaophthalmol.2013.4430
|View full text |Cite
|
Sign up to set email alerts
|

Vismodegib as Eye-Sparing Adjuvant Treatment for Orbital Basal Cell Carcinoma

Abstract: If these lesions were at the level of the RPE, one would expect them to be visualized on FAF imaging. However, they were completely silent on FAF imaging, suggesting that they may be located deeper than the RPE, at the level of the choriocapillaris. We distinguished 3 types of lesions based on their multimodal imaging characteristics in APMPPE. Type 1 lesions seem to be located at the level of the choriocapillaris and are transient. Type 2 and 3 lesions are at the level of the RPE and are permanent.The pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 5 publications
1
37
0
Order By: Relevance
“…The authors stated that vismodegib was not effective in patients who received it for less than 3 months. Kahana et al reported in a letter to the editor of a single patient with an orbital BCC 10 years after initial excision who was treated with oral vismodegib for 4 months with a partial response and about 70% reduction in tumour size 12. The patient stopped treatment due to intolerable muscle spasms and surgery was carried out with globe-preservation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that vismodegib was not effective in patients who received it for less than 3 months. Kahana et al reported in a letter to the editor of a single patient with an orbital BCC 10 years after initial excision who was treated with oral vismodegib for 4 months with a partial response and about 70% reduction in tumour size 12. The patient stopped treatment due to intolerable muscle spasms and surgery was carried out with globe-preservation.…”
Section: Discussionmentioning
confidence: 99%
“…All three cohorts did not meet the primary efficacy end points, predefined as CHC >50% in cohorts 1 (received vismodegib for 12 weeks before MMS) and 3 (received vismodegib for 8 weeks on/4 weeks off/8 weeks on before MMS) and CHC >30% in cohort 2 (received vismodegib for 12 weeks followed by 24 weeks of observation before MMS). Although other smaller studies have shown tumor size reduction with vismodegib therapy, convincing data from larger trials supporting the neoadjuvant use of HPIs is currently lacking [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…5 In the periocular and orbital area, vismodegib has been used as a medical or adjuvant therapy to decrease the tumor size, in the latter case to render it amenable to globe-sparing excision. 68 In this report, we analyze our results in using vismodegib for the treatment of basal cell carcinoma with orbital extension and/or extensive periocular involvement.…”
Section: Introductionmentioning
confidence: 99%